In vitro pediculicidal and ovicidal activity of an extract and oil from fruits of Melia azedarach L. - Carpinella, Maria Cecilia (2007)
Background: Head louse infestation is difficult to control because of increasing lice resistance to synthetic pediculicidal drugs. Objective: To test the activity of extract and oil obtained from fruits of Melia azedarach L. against the head louse Pediculus humanus capitis. Methods: A filter paper diffusion bioassay was carried out in order to determine the pediculicidal and ovicidal activity of extract and oil from M azedarach L. fruits. Results: Both vegetable products, tested either individually or in combinations, showed high levels of mortality on adult lice, with values ranging between 62.9% and 96.5%. The highest mortality rate was obtained with a combination of 20% ripe fruit extract with 10% ripe fruit oil. A formulation made with both extract and oil at 10% plus the addition of emulsifier and preserving agents showed 92.3% pediculicidal activity. The products were also successful in delaying or inhibiting nymph emergence, with the formulation being the most effective, with a complete inhibition of emergence. Limitations: Because adult lice are sensitive to starvation and therefore control mortalities are often higher than 20% in tests with field specimens, the results may not reflect the direct effect of the extract. Conclusions: These results demonstrate the possibility of using Melia products for controlling head lice, which are difficult to control because of their resistance to the currently used anti-louse agents.